Des tâches policières privatisées à une police grise : quatre recherches belges en la matière - Van Outrive, Lode (Criminologie, 1998)
This article summarizes the combined results of four branches of research concerning the privatization of policing tasks and the interaction between private agencies and police conducted between 1988 and 1997 in Belgium. The first segment focused on private detectives. A second research segment converged on the evolution of specialized investigations in insurance fraud. A third branch was aimed at the lack of legal protection available to citizens that had been subject to private investigations. The final segment consisted of an analysis of " grey policing". All research segments developed from a certain number of hypothesis and were based exclusively on qualitative research methods. Results from each segment have been assessed alongside established theories.